Design, modelling and analysis of a hybrid-magnet variable-flux PMSM with variable series-parallel magnetic circuit - Guangyuan Qiao; Ping Zheng; Mingqiao Wang; Faliang Liu; Yong Liu (Energy Reports, 2022)
Variable-flux permanent magnet synchronous machines (PMSMs) which use low-coercive-force permanent magnets have gained a lot of attention as a perspective alternative in the variable-speed driving application for their advantages of operating with improved efficiency in higher speed through adjusting the variable-flux PMSMs’ magnetization states. A hybrid-magnet variable-flux machine which has the variable series-parallel magnetic circuit is investigated. Magnetization state and magnetic circuit type of this variable-flux PMSM are adjustable. This machine’s equivalent magnetic circuit (EMC) model at different magnetization states is established and evaluated. This model can precisely represent the complicated and changeable magnetic circuit in variable-flux PMSMs and provide an effective way for the operating principle and performance analysis. The electromagnetic performances are investigated in detail. The magnetization state variation’s range is wide. Magnetizing/demagnetizing current is small. By fully using reluctance torque, variable-flux PMSM’s torque ability improves greatly. The ratio of high efficiency area in total torque-speed operating area increases obviously. The efficiency during high speed operation also increases. This machine has advantages and overcomes limitations of variable-flux machine which has series magnetic circuit or parallel magnetic circuit.